Managerial Styles and Digital Innovation for Sustainable Business Growth - Dušanka Paspalj (Journal of Agronomy, Technology and Engineering Management)
In the evolving business landscape, managerial styles and digital innovation are crucial drivers of sustainable business growth. Effective management influences decision-making, resource optimization, and adaptability, while digital technologies enhance operational efficiency, automate processes, and improve strategic insights. Transformational and participative management styles foster an environment that supports technological adoption, sustainability initiatives, and innovation. The integration of contemporary information technologies, such as big data analytics, cloud computing, and artificial intelligence, allows organizations to streamline processes, reduce costs, and enhance competitiveness. Additionally, sustainable leadership emphasizes ethical decision-making, corporate responsibility, and long-term business viability. By leveraging digital transformation and effective managerial approaches, organizations can enhance sustainability, improve resilience, and achieve a competitive advantage in a rapidly changing market. This paper explores the dynamic interaction between managerial styles and digital innovation, demonstrating their collective impact on corporate sustainability and business success.